Measurement Of Electrical Parameters On Iot-Based Main Generators For Safe Operational Feasibility - Prastyo, Herru; budijanto, arief; Winardi, Slamet (NAROTAMA UNIVERSITY, 2024)
The generator is the main source of electricity on the ship which will power all activities on the ship. With an electricity source supplied by a generator, human work will become lighter because of the help of electrical energy. In order for the generator to work well, it requires maintenance and must always be well controlled, so that the parameters produced by the generator must always be maintained by monitoring these parameters automatically using the ESP32 microcontroller. The parameters measured are current, voltage, power, frequency, work factor, KWh, RPM, temperature and vibration. By measuring the magnitude of these parameters, they can later be used as variables for maintenance and repair of the generator. The sensor used to measure the electrical parameters is the PZEM004t module because it can measure all generator electrical quantities, while temperature uses the DS18B20 sensor and vibration uses the SW420 sensor module. Then to measure the RPM using a potentiometer. The measurement results are displayed on a smartphone screen on the bridge using Internet of Things (IoT) technology sent from the engine room.